253 Stereotactic ablative radiotherapy in oligometastatic gynaecological malignancies. (13th November 2020) - El-Modir, A; Zarkar, A; Ghafoor, Q; Good, J; Sherriff, J; Yahya, S; Watkins, S; Karanam, S
Abstract : Objectives: Stereotactic Ablative Radiotherapy (SABR) is emerging as a treatment option for patients with oligometastatic solid tumours. The primary aim of this approach is local control and improving progression free survival (PFS). We report a single institution clinical outcomes. Methods: 42 lesions from 28 patients with relapsed oligometastatic gynaecological cancers (endometrium = 13, ovary = 7, cervical = 6, vulva = 1 and Vagina = 1) were treated with SABR, delivered using both cyberknife and VMAT. Treatment was delivered using a median of 4 fractions to a median dose of 45 Gy. Response was assessed with repeat imaging. CTCAE system 5.0 was used to assess acute and late toxicity. Results: Mean age was 67 years. Target lesions were lung = 13, pelvic node = 12, para-aortic node = 11, bone = 2, porta-hepatis node = 2, liver = 1, and peritoneal mass = 1. After a median follow-up of 17 months, 50% of the lesions had a partial response (PR), 12% had a complete response (CR), 28.5% were stable (SD), and 9.5% has progressive disease. Lesions greater than 30 mm had unfavourable outcome. Median PFS was 11.2 months. Median survival (OS) has not been reached. 2 patients experienced grade 3 toxicity. Conclusions: SABR for patients with relapsed oligometastatic gynaecological cancers is a safe treatment with promising results in terms of local control and PFS. As distant progression remains the primary mode of failure in these patients, the combination of SABR and systemic therapies requires evaluation in randomised controlled trials.